2013
DOI: 10.1111/j.2040-0209.2013.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Outside the Box: An Alternative Framework for Analysing Social Protection Programmes

Abstract: Summary The evidence base on social protection programmes is expanding rapidly, largely pointing towards their positive impacts. Most evaluations rely heavily on quantitative techniques and experimental methods to allow for attribution of impacts. In this paper, we argue that new ways of investigation and analysis are needed to expand and deepen the evidence base in support of improved design and implementation of social protection. Greater emphasis on qualitative research, mixed methods and participatory eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…The shifts in gender norms created by the opening up of economic opportunities and socio-cultural changes through NGO interventions, the Christian church, and education are being resisted by some men, especially of the older generation. Policy and interventions that involve or target women can impact on social dynamics and conflict (Devereux et al 2013), highlighting the need to be sensitive to cultural norms and fine-scaled relationships. As Hodgson (2001) has argued, without this sensitivity, external interventions can ignore aspects of women's power and add weight to gender inequalities.…”
Section: Diversity and Change In Maasai Well-being Conceptionsmentioning
confidence: 99%
“…The shifts in gender norms created by the opening up of economic opportunities and socio-cultural changes through NGO interventions, the Christian church, and education are being resisted by some men, especially of the older generation. Policy and interventions that involve or target women can impact on social dynamics and conflict (Devereux et al 2013), highlighting the need to be sensitive to cultural norms and fine-scaled relationships. As Hodgson (2001) has argued, without this sensitivity, external interventions can ignore aspects of women's power and add weight to gender inequalities.…”
Section: Diversity and Change In Maasai Well-being Conceptionsmentioning
confidence: 99%
“…Accordingly their evaluations have been preoccupied by measuring changes in beneficiaries' income, nutrition, health or education as they are not only clearly linked to economic growth, but also relatively easier to measure and quantify. Concentrating on these material effects, evaluations of cash transfers have indeed produced robust evidence that these programmes do work in terms of material wellbeing (Devereux et al, 2013;MacAuslan & Riemenschneider, 2011). However, it is increasingly acknowledged that not only do poverty and 2 F. Samuels & M. Stavropoulou vulnerability have multiple, including psychosocial, dimensions (Walker et al, 2013), but also that cash transfers can have effects that exceed their original material objectives (Devereux et al, 2013).…”
Section: Development and Psychosocial Wellbeingmentioning
confidence: 99%
“…Some studies have found that cash transfers increased household tensions and domestic violence as well as tensions between beneficiaries and non-beneficiaries with negative wellbeing effects (Devereux et al, 2013). Thus in South Africa, female recipients of the child transfer reported being looked down on by non-recipients and facing negative comments such as being lazy or unwilling to work (Hochfeld & Plagerson, 2011).…”
Section: Some Limitations In Terms Of Psychosocial Wellbeingmentioning
confidence: 99%
“…(2013) for diversity of considerations in welfare provision; and Devereux et al (2013) for multiplicity of factors in evaluating policy. Other factors promoting diversity include the ideational and institutional as in Buxton (2013) for social policy in Venezuela and health provision in Thailand, Yivayanond and Hanvoravongchai (2013), and Brazil, d'Ávila Viana and da Silva (2013).…”
Section: Puts Itmentioning
confidence: 99%